Chaos in dynamical systems - Ott, Edward (Cambridge University Press, 2002)
This book incluces the change of new material on riddled basins of attraction, phase locking of globally coupled oscillators, fractal aspects of fluid advection by Lagrangian chaotic flows, magnetic dynamos, and strange nonchaotic attractors.